Monitoring succinoglycan production in single Sinorhizobium meliloti cells by Calcofluor white M2R staining and time-lapse microscopy. (1st February 2018) - Jofré, Edgardo; Liaudat, Juan Pablo; Medeot, Daniela; Becker, Anke
Highlights: A method for monitoring the succinoglycan production in single cells is reported. The method combines the use of Calcofluor (CF) and time-lapse microscopy. The reported method is simple, non-time consuming and inexpensive. It could be applicable to other bacteria producing β-(1 → 3), β-(1 → 4) polysaccharides. CF detection could be combined with the monitoring of mCherry and GFP proteins. Abstract: Here, we describe a simple, non-time consuming and inexpensive method for monitoring of Calcofluor white M2R-binding exopolysaccharides in individual bacterial cells. This method was demonstrated by time-lapse microscopy of succinoglycan-producing cells of the plant-symbiotic alpha-proteobacterium Sinorhizobium meliloti . The method is most likely applicable to other bacteria producing β-(1 → 3) and β-(1 → 4) linked polysaccharides.